Relationships of maternal vitamin D status and feeding practices with development of allergic diseases and malnutrition among infants - Woon, Fui Chee (2020)
Allergic diseases and malnutrition are two of the most common and earliest developing health issues in early childhood. The high prevalence is concerning because of the implications of allergic diseases and malnutrition on long-term health and well-being of the infants. This study aims to determine the associations of maternal vitamin D status during late pregnancy and feeding practices with the development of allergic diseases and malnutrition in infants during the first year of life. In this prospective cohort study, 535 third-trimester pregnant women were recruited from six selected government health clinics at the state of Selangor and Federal Territory of Kuala Lumpur, Malaysia. Their blood sample was collected to determine their serum 25(OH)D concentrations. After delivery, 380 motherinfant pairs completed the 3, 6, and 12 months follow-up. At each follow-up, infant feeding practices and allergic outcomes were assessed based on parental reports. Infant’s anthropometric data were extracted from medical records. At 12 months of age, serum samples were collected from the infants to determine their sensitisation against food allergens. Vitamin D insufficiency and deficiency were observed in 48.8% and 42.8% of the pregnant women, respectively. About 46.6% of the infants were exclusively breastfed until 6 months, 97.1% had timely initiation of complementary feeding, 10.5% met minimum dietary diversity (MDD) at 6 months, and 54.5% met MDD at 12 months. About 27.6% of the infants had eczema, 20.8% had parentreported food allergy (FA), 3.8% had IgE-mediated FA, and 27.4% had food sensitisation during the first year of life. The prevalence of stunting, wasting, underweight, and overweight at 12 months was 16.3%, 7.6%, 11.6%, and 1.8%, respectively. After adjustment for confounders, study sites, and mother-infant pairs clustering effect, results from a multivariable generalised linear mixed model showed that maternal vitamin D deficiency was associated with higher odds of parent-reported FA in infants (OR = 1.82, 95% CI = 1.02-3.23). Higher odds of food sensitisation were found in infants who met MDD at 6 months (OR = 2.62, 95% CI = 1.10-6.24). No associations were found for maternal vitamin D status and other feeding practices with eczema, IgE-mediated FA, and malnutrition. Parent-reported FA was associated with higher odds of wasting in infants (OR = 2.60, 95% CI = 1.17-5.79), while no associations were found for other allergic outcomes with malnutrition. Results from the structural equation modelling showed that the relationships between maternal vitamin D deficiency (- 0.29, 95% CrI = -0.55, -0.05) and wasting in infants (0.27, 95% CrI = 0.07, 0.51) were fully mediated by parent-reported FA after adjustment for confounders. In conclusion, the present study demonstrates the important role of parentreported FA as a mediator in explaining the relationships between maternal vitamin D deficiency during late pregnancy and wasting in infants during the first year of life. The present study suggests that nutrition education and counselling for pregnant women and lactating mothers should emphasise on the importance of vitamin D and their sources, common food allergens, and management of FA to ensure optimal growth in infants.